Management in Emerging versus Developed Countries: A Comparative Study from an Indian Perspective - Nigam, Roli (2011)
With the opening up of the Indian economy, many Indian multinational companies have started operating abroad in more developed countries. This raises questions about which culture they follow in subsidiaries in developed countries. The Indian management culture may be seen through their multinational’s human resource management practices. The management culture may not necessarily have the same effect or hold similar values in the subsidiaries of Indian multinational companies located in developed countries because of the many cultural and institutional differences. Several studies have been conducted from the point of view of developed countries’ multinational companies and their management, but scarcely any from the Indian perspective. In view of the opening up of the Indian economy, it becomes extremely important to make an attempt to understand Indian management and examine the best cross-cultural strategies for optimal organizational performance across borders in the future.